WEB-BASED PENSION FUND MANAGEMENT SYSTEM (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Given the discouraging record of the traditional pension system and the limited coverage of the private-sector pension schemes, there is need for robust web-based pension fundmanagement system that can handle the pension process efficiently. This work focus on the design and implementation of a web-based pension fund management application toreplace the manual system, thus getting rid of the hurdles involved in the traditional pension management process.